2013
DOI: 10.1007/s00442-013-2806-5
|View full text |Cite
|
Sign up to set email alerts
|

Complex life cycles in a pond food web: effects of life stage structure and parasites on network properties, trophic positions and the fit of a probabilistic niche model

Abstract: Most food webs use taxonomic or trophic species as building blocks, thereby collapsing variability in feeding linkages that occurs during the growth and development of individuals. This issue is particularly relevant to integrating parasites into food webs because parasites often undergo extreme ontogenetic niche shifts. Here, we used three versions of a freshwater pond food web with varying levels of node resolution (from taxonomic species to life stages) to examine how complex life cycles and parasites alter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
18
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 53 publications
4
18
0
Order By: Relevance
“…A growing body of theoretical work (Barbour et al 2016, Gilljam 2016, Zee and Schreiber 2017 documents the changes that this intraspecific variation can make to ecological networks, but empirical data on the topic are still relatively poor (Woodward et al 2010, Gilljam et al 2011. In particular, there has been little work identifying the structural network consequences of intraspecific variation that arises as a result of organisms moving through their life cycle, life stage variation, despite its prevalence in nature (Preston et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…A growing body of theoretical work (Barbour et al 2016, Gilljam 2016, Zee and Schreiber 2017 documents the changes that this intraspecific variation can make to ecological networks, but empirical data on the topic are still relatively poor (Woodward et al 2010, Gilljam et al 2011. In particular, there has been little work identifying the structural network consequences of intraspecific variation that arises as a result of organisms moving through their life cycle, life stage variation, despite its prevalence in nature (Preston et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…trait-mediated indirect effects). Furthermore, because the trophic level of the cercariae can be interpreted as equivalent to their previous feeding stage, this represents a distinct trophic interaction from that occurring between tadpoles and dragonflies (Preston et al, 2013a). Although dragonflies also eat damselflies, previous research has indicated that caged dragonflies do not influence damselfly foraging activity, which is the primary mechanism by which we expected damselflies to influence parasite infection (Stoks et al, 1999;Stoks, 2001).…”
Section: Study Systemmentioning
confidence: 82%
“…Damselfly larvae (Enallagma sp. Furthermore, because the trophic level of the cercariae can be interpreted as equivalent to their previous feeding stage, this represents a distinct trophic interaction from that occurring between tadpoles and dragonflies (Preston et al, 2013a). were selected as predators of R. ondatrae cercariae, because previous small-scale laboratory studies have shown that they actively consume cercariae even in the presence of alternative prey and can reduce transmission (Schotthoefer, Labak & Beasley, 2007;Orlofske et al, 2012).…”
Section: Study Systemmentioning
confidence: 99%
“…Like all parasites, hyperparasites can impact population size and fitness of their hosts (Sieber and Hilker, 2011; Allen and Bokil, 2012; Preston et al, 2014). Some hyperparasites can infect persistent structures of their hosts, for example oospores, resistant sporangia, or resting spores (Gleason et al, 2010).…”
Section: Size Control Of Host Populations By Hyperparasitesmentioning
confidence: 99%
“…Adding links to food webs, such as parasites, hyperparasites, and both of their associated niches, might also add to the stability of a particular web (Hudson et al, 2006; Lafferty et al, 2006, 2008). Parasites with life cycles involving ontogenetic niche shifts—such as hyperparasites—impact food web structures more and potentially negatively because specialized life cycle stages are more prone to secondary extinction than generalist stages (Preston et al, 2014). Such ontogenetic effects can be found in zoosporic hyperparasites: different types of zoospores, or zoospores formed by different species can have considerably different swimming patterns (Lange and Olson, 1983) or serve different purposes like long or short distance dispersal (Neuhauser et al, 2011a).…”
Section: Food Websmentioning
confidence: 99%